Comparative Analysis of Repair Policy and Preventive Maintenance Policy Methods in Machine Maintenance on the Production Floor of PT. Metro Riau - Sugandi, Bagus Ahmad; Hamdy, Muhammad Ihsan; Taslim, Rika; Nofirza, Nofirza; Nur, Muhammad (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2025)
PT. Metro Riau is a newspaper printing company facing significant challenges due to high machine breakdown rates, which have impacted maintenance costs and production output. This study aims to compare machine maintenance costs using repair policy and preventive maintenance policy methods and provide recommendations for the most efficient maintenance approach. The data utilized includes types of breakdowns, maintenance costs, and production rates during the 2023 period. The research employs a quantitative analysis method to calculate repair and preventive maintenance costs based on the probability of breakdowns for each type of machine. The findings reveal that for type A breakdowns, the repair policy is more cost-effective, with a maintenance cost of IDR 143,829 compared to IDR 176,384 for the preventive maintenance policy. Conversely, for type B and C breakdowns, the preventive maintenance policy is more efficient, with costs of IDR 259,616 and IDR 375,950, respectively, compared to the repair policy. Based on these results, it is recommended to implement the repair policy for type A breakdowns and the preventive maintenance policy for types B and C. This combined approach is expected to reduce maintenance costs while enhancing the reliability of the company's production machinery.